2012
DOI: 10.1684/ecn.2012.0312
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β a potential factor for discriminating between thyroid carcinoma and atrophic thyroiditis

Abstract: Interactions between cytokines and others soluble factors (hormones, antibodies. . .) can play an important role in the development of thyroid pathogenesis.The purpose of the present study was to examine the possible correlation between serum cytokine concentrations, thyroid hormones (FT4 and TSH) and auto-antibodies (Tg and TPO), and their usefulness in discriminating between different thyroid conditions. In this study, we investigated serum from 115 patients affected with a variety of thyroid conditions (44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Also, there was a highly significant increase in FT4 obtained from thyroiditis group as compared to thyroid cancer group (p=0.04). This result was confirmed by data obtained by several authors [10,11].…”
Section: Effect Of Gender On Tmda Level In Different Studied Groupssupporting
confidence: 89%
“…Also, there was a highly significant increase in FT4 obtained from thyroiditis group as compared to thyroid cancer group (p=0.04). This result was confirmed by data obtained by several authors [10,11].…”
Section: Effect Of Gender On Tmda Level In Different Studied Groupssupporting
confidence: 89%
“…and decreased levels of IL-1β, IFN-α and TGF-β1 in PTC patients compared with controls, in agreement with previous studies regarding IL-6 10,22 and IL-1β levels. 9 The multiple logistic regression analysis further revealed that only IFN-α and TGF-β1 significantly and efficiently discriminated PTC patients from controls (Figure 1). tumour growth and metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…1,6 Thyroidectomy is frequently performed in these inconclusive cases for definitive identification; however, patients undergoing surgery without malignant tumours are exposed to unnecessary risk, demanding the search for non-invasive biomarkers to improve risk assessment and preoperative diagnosis. 7 There is a recognised association between the inflammatory microenvironment and TC, 8 and altered levels of both regulatory and inflammatory cytokines in PTC have already been reported, including interleukins (IL)-1β, 9 IL-6 10 and interferon (IFN)-α. 11 Certain cytokines released by inflamed tissues can reciprocally influence the expression of the human leucocyte antigen-G (HLA-G) molecule, 12 which is an important immunomodulator of the tumoural immune response.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with a result of Marchiori and coworkers (2015) who showed elevate in the serum grade of IL-1β in hypothyroid Patients. As well as, Kammoun-Krichen et al (2012) revealed elevation in the level of IL-1β in hypothyroid patients and suggested the possibility of using it to distinguish between thyroid diseases. On the other hand, the present result is disagreement with the result reported by Phenekos and colleagues (2004) who found a decrease in IL-1β level in Hashimoto patients than Graves's disease (GD) and control.…”
Section: Resultsmentioning
confidence: 89%
“…Actually, it is famed that IL-1β effect the work of thyroid cells by reducing the term of Tg and TPO, that intensity of IL-1β alter thyroid epithelial hardship of human thyrocytes by changing the expression, localization and regulation of cross proteins, supported the remarkable part played by IL-1β in thyroid pathogenesis (Kammoun-Krichen et al, 2012). About Il-1β in patients group with periodontitis, Raunio et al (2007) and Hajishengallis (2014) reported that the rise in serum IL-1β might be demonstrated both by seep of the locally generated IL-1β from the inflamed periodontal region and by systemic output in reply to the systemically sparse antigen capacity.…”
Section: Resultsmentioning
confidence: 99%